Novel therapies in melanoma. (December 2011) - Scheier, Benjamin; Amaria, Rodabe; Lewis, Karl; Gonzalez, Rene
The incidence of cutaneous melanoma is on the rise worldwide despite increasing awareness and vigilance towards prevention by the lay public and health professionals. Melanoma is easily curable by surgical excision when detected early, but it is nearly incurable when discovered in its later stages owing to resistance to treatment. Unfortunately, treatment options traditionally used in melanoma have not shown a survival benefit. However, as the understanding of tumor biology and metastatic growth evolves, new therapeutic options for metastatic melanoma have shown impressive survival benefit. The blockade of cytotoxic T-lymphocyte antigen 4 (CTLA-4) by use of the monoclonal antibody, ipilimumab (Yervoy™, Bristol-Myers Squibb), produces favorable antitumor immune system responses and was recently approved by the US FDA for use in patients with advanced melanoma. In addition, targeting components of the MAPK pathway have also demonstrated survival advantage in patients with BRAF -mutated melanoma and vemurafenib (Zelboraf™, Plexxikon/Roche) was approved by the FDA in August 2011 for the first-line treatment of both metastatic and unresectable melanomas for patients whose tumors have V600E mutations in the BRAF gene.